Pekanbaru Public Service Innovation Ã¢â‚¬Å“Pekanbaru Dalam GenggamanÃ¢â‚¬Â Of The Pekanbaru City Communications Informatics Statistics And Coding Department - Rahman, Khairul; Eka Anjani Sapitri (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
To improve public services, the Pekanbaru City government, through the Pekanbaru City Information, Statistics, and Coding Communication Service, is making innovative efforts by providing integrated digital information and services that aim to make it easier for the public to get digital public services called Pekanbaru in their grasp. Pekanbaru dalam genggaman is an information system that collects all public service and information applications within the Pekanbaru City government. Good and quality service implies satisfaction for the community which is a benchmark for the success of government administration. Innovation is a form of renewal in government administration and aims to improve the performance of regional government administration. This research aims to find out how innovative Pekanbaru public services are in Ã¢â‚¬Å“Pekanbaru Dalam GenggamanÃ¢â‚¬Â of the Pekanbaru City Information, Statistics, and Coding Communication Service. In this research, qualitative descriptive research methods were used with interview, observation, and documentation data collection techniques. Activities in qualitative data analysis are carried out interactively and take place continuously at each stage of the research until completion. The results of this research show that Pekanbaru public service innovation Ã¢â‚¬Å“Pekanbaru dalam genggamanÃ¢â‚¬Â of the Pekanbaru City Information, Statistics, and Coding Communication Service has not run optimally, the services provided have not fully targeted the community and have not been fully integrated. This is based on the results of an analysis of five indicators of public service innovation, namely relative advantage, suitability, complexity, possibility of being tried, and ease of observation. There are still several indicators that have not been achieved in these five indicators, namely those related to complexity, possibility of trying, and ease of observation so the level of adaptation in implementation is not evenly distributed.